The work of programme managers in state-funded employer-driven Swedish higher VET - Johanna Köpsén (International Journal for Research in Vocational Education and Training (IJRVET), 2022)
Context: Swedish Higher Vocational Education (HVE) is organised as state-funded programmes provisioned by both public and private education providers in close relation to employers. In HVE programme managers have responsibilities like those that often are vested in vocational teachers. They are responsible both for the day-to-day work of provision and the continuous development of the programme and its syllabi. This article presents a study investigating the work of programme managers, focusing on their work with creating and updating syllabi and on their work organising the students' training. Methods: Five programme managers responsible for five diverse HVE programmes have been interviewed and the syllabi of these programmes have been examined. The analysis is based on a Bernsteinian theoretical perspective focusing on recontextualisation of knowledge for pedagogic discourse by different stakeholders as agents who have different basis for their actions. The study first establishes what knowledge make up the programmes to inform the understanding of what training the programme managers are tasked with organising, then examines how the programme managers take part in selecting knowledge for course syllabi, and how they organise the teaching of these syllabi in in their programmes. Findings: The knowledge that has been recontextualised for pedagogic discourse in the studied programmes is most often vocationally specific or context bound in relation to a particular occupational field. The syllabi are related to clearly defined jobs. The findings highlight how practice thus in several ways may be difficult for programme managers without work experience in the relevant occupational field or knowledge in relation to it. Not only in the work of forming and updating curricula, but also as they must be able to navigate the relevant sector of business and industry to engage appropriate employers for collaborations and to hire teaching staff. Conclusion: The findings presented in this article show that local autonomy allows for major differences regarding knowledge in syllabi and the organisation of learning between programmes within the same nationally organised VET system. This is salient even with a small number of programmes having been studied. This strongly support the importance of examining what happens in autonomous local contexts of VET provision and asking who has influence over publicly funded education in this sort of contexts, and on what these stakeholders base their actions.
Keywords: 330; VET; Vocational Education and Training; Continuing Vocational Education and Training; Planning of Education and Training; Vocational Teachers; Education Industry; Relationship